Directional decomposition and properties of thunderstorm outflows. Issue 189 (June 2019) - Zhang, Shi; Solari, Giovanni; Burlando, Massimiliano; Yang, Qingshan
Abstract: Thunderstorm outflows are usually analysed by decomposing their horizontal velocity into a slowly-varying mean part and a residual fluctuation; in this framework the wind direction is often examined qualitatively but disregarded quantitatively. This is incoherent with the traditional analysis of synoptic wind speeds, where the mean velocity and direction are first determined, then the fluctuations are decomposed in terms of longitudinal and lateral turbulence components. Aiming to overcome these shortcomings, a novel directional decomposition strategy is formulated here, which makes the study of thunderstorm outflows and synoptic winds fully coherent. The results provided by the classic and novel decomposition rules are first compared and elucidated with reference to a couple of real thunderstorm and synoptic wind velocity records. Later on, they are applied to a broad class of thunderstorm outflow records whose statistical properties are investigated. The novel approach is strategic to carry out directional analyses of the dynamic behaviour of structures in terms of alongwind and crosswind response. Highlights: The classical decomposition rule of thunderstorm outflows disregards wind direction. Classical synoptic wind and thunderstorm outflow decomposition rules are incoherent. A novel directional rule is formulated that overcomes the above shortcomings. The novel rule is strategic to carry out directional analyses of the structural response.